EVALUATING THE DETERMINANTS OF PESTICIDE RESIDUES IN VEGETABLES: A CASE OF LEMON MARKET IN PAKISTAN - Abedullah1; S. Kouser (Journal of Animal and Plant Sciences, 2020)
In developing countries, vegetable markets are inefficient in terms of information exchanges between producers and consumers on food safety attributes. This study attempts to investigate the determinants of pesticide residues and estimates information efficiency of vegetable market, using socioeconomic and biophysical data collected from a representative sample of 360 farmers in Pakistani Punjab. Chromatography technique is employed to quantify pesticide residues in okra, brinjal, spinach and cauliflower. A large proportion of spinach samples (83%), followed by okra (72%), brinjal (60%) and cauliflower (50%) have surpassed the maximum residue limits of pesticides, implying that they are lemons. Results of pesticide residue model show that magnitudes of pesticide residues in vegetables vary with pesticide quantity and spray interval at the farm level. Results of information efficiency model reveal that vegetable prices are negatively but insignificantly correlated with pesticides residues, implying that vegetable market is a lemon market in Pakistan. Proper implementation of food safety standards and product labeling may help to provide safe vegetables to consumers.
Keywords: Vegetables; information asymmetry; lemons market; gas chromatography; pesticide residues; food safety; Pakistan